EFEKTIVITAS PELAKSANANAN DEBAT KANDIDAT CALON KEPALA DAERAH DAN WAKIL KEPALA DAERAH DI KABUPATEN OGAN KOMERING ULU TAHUN 2024 - Dela Ariza; Marratu Fahri; Yahnu Wiguno Sanyoto (Jurnal Riset Multidisiplin Edukasi, 2026)
(Bawaslu) stated that the General Elections Commission (KPU) was unprofessional due to the incomplete second The research background emerged because the oversight results from the OKU public debate. The 2024 regional head election (Pilkada) results were also not positively received by Candidate Pair 01 (Yudi-Yenny), who lost by a margin of 3,809 votes to Candidate Pair 02. They claimed there were violations and that the KPU was not neutral. This study aims to determine the effectiveness of the 2024 regional head and deputy regional head candidate debates, using a descriptive qualitative method through observation, interviews, and direct documentation of the OKU Regency KPU. The research was conducted from June 1 to June 3 2025. The research findings show four main indicators: (1) Achievement of objectives contributed positively to political transparency and voter education, but was not yet optimal in helping the public comprehensively assess the candidates; (2) Timeliness was problematic due to delays and uneven time allocation among candidates; (3) Output quality was negatively affected by the walk-out action of the YPN-YESS candidate pair, which made information incomplete and unrepresentative; (4) Implementation efficiency was not yet optimal due to various management weaknesses. The research conclusion states that the 2024 OKU Regency Pilkada debate was not yet effective and optimal, so comprehensive evaluation and improvement are needed. The recommendations provided are as follows: for KPU OKU to improve aspects of time, location, technical matters, and publication; for debate participants to enhance the substance of their presentations; for the government and stakeholders to support facilities and information dissemination; for the public to participate actively; and for subsequent researchers to expand the scope of study to political literacy and the influence of social media.